Gas-phase silicon-carbon negative electrode material of porous carbon base material

Through porous starch and sucrose coating technology, combined with nanoporous silicon/carbon composite materials and silicon acetylene CVD method, a high-performance porous carbon substrate gas-phase silicon carbon anode material was prepared, solving the complex process and high cost in the existing technology. The problem of insufficient performance has achieved the improvement of material stability and performance.

CN119252877APending Publication Date: 2025-01-03ZHEJIANG WESTON NEW MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411222964.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing gas-phase silicon carbon anode material has complex preparation processes and high cost, and is difficult to control cycle stability and volume expansion rates, which limits its large-scale application and performance improvement.

Method used

Porous starch is used as the basis of silicon/porous carbon composite materials, and a porous structure with a high specific surface area is formed by synergistic hydrolysis of α-amylase and glucoamylase. Combined with sucrose coating and preparation of nanoporous silicon/carbon composite materials, silicon is used. Carbon coating is carried out by acetylene CVD method to form a stable porous carbon substrate vapor phase silicon carbon anode material.

Benefits of technology

Improves the cyclic stability and electrochemical performance of the material, reduces production costs, simplifies the process flow, enhances the dispersion and conductivity of silicon nanoparticles, alleviates the problem of volume expansion, and improves the cycle life and performance consistency of the battery. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252877A_ABST
    Figure CN119252877A_ABST
Patent Text Reader

Abstract

The invention relates to a gas-phase silicon-carbon negative electrode material of a porous carbon base material, which comprises the following steps: preparing porous starch, preparing a silicon / porous carbon composite material, preparing a micron porous Mg2Si negative electrode, preparing a nano porous silicon / carbon composite negative electrode, performing carbon coating by a porous silicon acetylene CVD (Chemical Vapor Deposition) method, and controllably preparing the gas-phase silicon-carbon negative electrode material of the porous carbon base material. The gas phase precipitation method and the alloying method are creatively combined, the prepared negative electrode material has higher specific capacity and energy density, rapid transmission of lithium ions is facilitated, the stability of an electrode structure is kept, and the negative electrode material has the advantages of being good in cycle performance, high in safety, high in energy density and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a gas phase silicon-carbon negative electrode material of a porous carbon substrate. Background Art

[0002] As an important component of silicon-carbon negative electrode materials, porous carbon substrates have unique structures and excellent performance. In silicon-carbon negative electrode materials, porous carbon substrates can not only provide enough space to accommodate the volume expansion of silicon materials, but also serve as transmission channels for electrons and ions to improve battery performance. Gas-phase silicon-carbon negative electrode materials have broad application prospects in energy storage devices such as lithium-ion batteries due to their excellent performance characteristics. With the continuous expansion of markets such as new energy vehicles and portable electronic devices, the demand for high-performance and high-energy-density battery materials is increasing, and gas-phase silicon-carbon negative electrode materials are expected to become an important development direction for future battery materials.

[0003] Gas-phase silicon-carbon anode materials based on porous carbon substrates show great potential in the field of energy storage due to their unique structure and excellent performance. However, many challenges still need to be overcome to achieve their large-scale application. Although gas-phase silicon-carbon anode materials have many advantages, their complex preparation process and high cost are still the main factors restricting their large-scale application. In addition, how to further improve the cycle stability of the material and reduce the volume expansion rate also need to be solved. Summary of the invention

[0004] In view of the above problems, the present invention provides a gas phase silicon-carbon negative electrode material based on a porous carbon substrate.

[0005] The first technical purpose of the present invention is to provide a method for preparing a silicon / porous carbon composite material.

[0006] The second technical purpose of the present invention is to provide a method for preparing porous silicon acetylene carbon coating by CVD method.

[0007] The third technical purpose of the present invention is to provide a gas-phase silicon-carbon negative electrode material based on a porous carbon substrate.

[0008] The present invention provides a gas-phase silicon-carbon negative electrode material on a porous carbon substrate, comprising the following steps: preparation of porous starch, preparation of silicon / porous carbon composite materials, preparation of micron porous Mg2Si negative electrodes, preparation of nanoporous silicon / carbon composite negative electrodes, carbon coating of porous silicon by acetylene CVD method, and controllable preparation of gas-phase silicon-carbon negative electrode materials on a porous carbon substrate.

[0009] Preferably, step (1) preparation of porous starch The corn starch is added into a sodium hydrogen phosphate-citric acid buffer solution, stirred and mixed, and pretreated to obtain corn starch, α-amylase and glucoamylase are added into the pretreated starch suspension, and hydrolyzed on a magnetic stirrer, after the enzymatic hydrolysis, a large number of micropores are generated from the outside to the inside of the raw starch, forming porous starch and starch slurry with high specific surface area and good adsorption performance, and the porous starch is separated by filtering; Step (2) Preparation of silicon / porous carbon composite material The porous starch prepared in step (1) and deionized water are added to a magnetic stirrer to obtain a starch suspension, and then the silicon solution is dispersed uniformly by ultrasonic treatment in advance to obtain a starch mixture in which silicon is inserted, and then a sucrose solution is added, and the mixture is dried in an oven to obtain a sucrose-coated composite material, and finally the porous starch / silicon / sucrose precursor is placed in an inert atmosphere of argon or nitrogen and carbonized at a high temperature, and the starch reacts during the vacuum carbonization process, thereby obtaining a high-capacity silicon / porous carbon composite material with good cycle performance; Step (3) Preparation of microporous Mg2Si negative electrode The Mg-55Si thin slice is polished by sandpaper from coarse to fine, and then ultrasonically cleaned with deionized water and ethanol to remove the oxide layer and attached impurities generated on the surface of the sample during wire cutting to avoid affecting the subsequent dealloying treatment; the polished and cleaned sample is then placed in a beaker containing sodium hydroxide solution, and the beaker is placed in a water bath for corrosion and then taken out, the sodium hydroxide solution attached to the surface of the sample is washed off, and the sample is placed in a vacuum drying oven for drying to obtain a micron porous Mg2Si negative electrode; Step (4) Preparation of nanoporous silicon / carbon composite negative electrode The microporous Mg2Si negative electrode prepared in step (3) is placed in a muffle furnace, and after heat treatment in an air atmosphere, a sample is taken out; the heat-treated sample is placed in a beaker containing a hydrochloric acid solution, and after corrosion at room temperature, the sample is taken out and the hydrochloric acid solution attached to the surface is washed off, and then dried in a vacuum drying oven to obtain a nanoporous silicon sample; a Tris buffer is prepared; the nanoporous silicon sample is weighed and placed in the buffer, and magnetically stirred to uniformly disperse the sample in the solution to form a suspension; dopamine hydrochloride is added to the suspension and magnetically stirred, and after washing and filtering with deionized water, the vacuum-dried sample is placed in a tubular furnace, and after passing argon gas to expel the air, the temperature is increased for carbonization, and the carbonization process is carried out in an argon protective atmosphere to obtain a nanoporous silicon / carbon composite negative electrode; Step (5) Carbon coating of porous silicon by acetylene CVD method A layer of the nanoporous silicon / carbon composite negative electrode prepared in step (4) is laid on the bottom of the quartz boat, and the quartz boat is placed in the middle position of the quartz tube of the tube furnace, and then the pipeline of the reaction system is connected; a mixed gas of Ar and C2H2 is introduced into the tube furnace, and the gas is heated at the same time, and then a constant temperature heat treatment is performed, and after the gas is naturally cooled to room temperature, the introduction of the mixed gas of Ar and C2H2 is finally stopped; Step (6) Controllable preparation of gas phase silicon-carbon negative electrode material on porous carbon substrate The silicon / porous carbon composite material prepared in step (2) and the porous silicon acetylene carbon-coated by CVD method in step (5) are added as precursors, and the precursors are placed in a tube furnace and heated in a CO2 atmosphere. After the reaction, the magnesium oxide in the intermediate product is removed by hydrochloric acid solution, and the gas phase silicon-carbon negative electrode material of the porous carbon substrate is obtained by washing, filtering and vacuum drying.

[0010] The first technical purpose of the present invention is achieved through the following technical solutions: Preferably, step (1) preparation of porous starch Corn starch is added to a sodium hydrogen phosphate-citric acid buffer solution with a pH value of 3-6, stirred and mixed, and pretreated at 45-55° C. for 25-30 minutes to obtain corn starch, α-amylase and glucoamylase are added to the pretreated starch suspension at a ratio of 1-2:2-4, and hydrolyzed on a magnetic stirrer at 40-45° C. and 150-180 r / min for 9-15 hours. After enzymatic hydrolysis, a large number of micropores are generated in the raw starch from the outside to the inside, forming porous starch and starch slurry with high specific surface area and good adsorption performance, which are filtered and separated to obtain porous starch.

[0011] The advantage of the present invention is that, through the synergistic action of α-amylase and glucoamylase, raw starch is hydrolyzed from the outside to the inside, generating a large number of micropores, and forming porous starch with a high specific surface area; this porous structure not only increases the specific surface area of ​​the material, but also provides more attachment points and reaction space for subsequent vapor phase silicon deposition.

[0012] The high specific surface area and good adsorption properties of porous starch help to better adsorb and fix silicon nanoparticles in the subsequent steps, and help to evenly distribute and firmly adhere silicon nanoparticles on the carbon substrate.

[0013] Preferably, step (2) preparation of silicon / porous carbon composite material The porous starch prepared in step (1) and deionized water (volume ratio of 1-3:95-100) are added to a magnetic stirrer at a constant temperature of 40-45°C, and a starch suspension is obtained at a stirring speed of 250-300 r / min. The silicon solution is then dispersed uniformly by ultrasonic treatment to obtain a silicon-intercalated starch mixture. After 1-3 hours, a sucrose solution is added and dried in an oven at 40-45°C to obtain a sucrose-coated composite material. Finally, the porous starch / silicon / sucrose precursor is placed in an inert atmosphere of argon or nitrogen and carbonized at high temperature. The starch reacts during the vacuum carbonization process to obtain a high-capacity silicon / porous carbon composite material with good cycle performance.

[0014] The advantage of adopting the present invention is that, through the porous starch, silicon nanoparticles can be uniformly and stably embedded in the porous structure to form a silicon / porous carbon composite material, thereby improving the dispersibility of the silicon nanoparticles and effectively alleviating the volume expansion problem of silicon during the charging and discharging process, thereby improving the cycle stability of the material.

[0015] The addition of sucrose solution further enhances the bonding between silicon nanoparticles and the porous carbon substrate. The carbon layer also provides additional conductivity and structural stability, which helps maintain the integrity of the material and the consistency of its performance during the charge and discharge process.

[0016] The second technical purpose of the present invention is achieved through the following technical solutions: Preferably, step (3) preparation of micron porous Mg2Si negative electrode The Mg-55Si thin slice was grinded and polished with sandpaper from coarse to fine, and then ultrasonically cleaned with deionized water and ethanol to remove the oxide layer and attached impurities generated on the surface of the sample during wire cutting to avoid affecting the subsequent dealloying treatment; the grinded, polished and cleaned sample was placed in a beaker containing 1-5wt.% sodium hydroxide solution, and the beaker was placed in a 65-70℃ water bath for corrosion for 1-5h and then taken out, the sodium hydroxide solution attached to the surface of the sample was washed off, and the sample was placed in a vacuum drying oven and dried at 65-70℃ for 8-12h to obtain a micron porous Mg2Si negative electrode.

[0017] The present invention has the advantage that the micron porous Mg2Si structure is conducive to the insertion and extraction of lithium ions, thereby improving the electrochemical performance of the negative electrode material. By adjusting the concentration of the sodium hydroxide solution and the corrosion time, the pore structure of the Mg2Si negative electrode can be finely controlled, including the pore size, distribution and connectivity, thereby further optimizing the performance of the negative electrode material. The micron porous Mg2Si negative electrode can provide more lithium storage sites due to its porous structure and high specific surface area.

[0018] Preferably, step (4) preparation of nanoporous silicon / carbon composite negative electrode The micron porous Mg2Si negative electrode prepared in step (3) is placed in a muffle furnace at 400-550°C, and heat treated for 15-20 hours in an air atmosphere, and then the sample is taken out; the heat-treated sample is placed in a beaker containing 1-5wt.% hydrochloric acid solution, and corroded at room temperature for 12-24 hours, and then the sample is taken out, and the hydrochloric acid solution attached to the surface is washed off, and then dried in a vacuum drying oven to obtain a nanoporous silicon sample; a Tris buffer solution (pH=6-8.5) with a concentration of 0.1-0.5M is prepared; and a 100% MgCl2O3 solution is added to the sample. Weigh 1.0-5.0g of nanoporous silicon sample and put it into 95-100ml buffer solution, stir magnetically for 25-30min, and evenly disperse the sample into the solution to form a suspension; add 1.0-5.0g of dopamine hydrochloride into the suspension, stir magnetically for 12-24h, wash with deionized water, filter, and vacuum dry for 6-12h; put the vacuum-dried sample into a tubular furnace, introduce argon gas to exhaust the air, and then heat and carbonize. The carbonization process is carried out in an argon protective atmosphere at a rate of 1-5℃min -1 The temperature is raised to 750-800°C at a rate of 100°C and kept at this temperature for 1-3 hours to obtain a nanoporous silicon / carbon composite negative electrode.

[0019] The invention has the advantages that the chemical reagents such as hydrochloric acid and Tris buffer used in the whole preparation process are used in moderate amounts, are easy to handle, and meet environmental protection requirements.

[0020] Through the polymerization of dopamine and subsequent carbonization treatment, a uniform carbon coating is formed on the surface of nanoporous silicon. This carbon coating not only improves the conductivity of the material, but also effectively alleviates the volume expansion of silicon during the charging and discharging process, thereby improving the cycle stability and structural integrity of the material.

[0021] Preferably, step (5) the porous silicon is coated with carbon by acetylene CVD method. A layer of nanoporous silicon / carbon composite negative electrode prepared in step (4) is laid on the bottom of the quartz boat, and the quartz boat is placed in the middle position of the quartz tube of the tube furnace, and then the pipeline of the reaction system is connected; a mixed gas of Ar and C2H2 is introduced into the tube furnace, and the gas flow rate is 300-350ml / min. At the same time, the gas is heated, and the heating rate is set to 5-10℃ / min, and the temperature is gradually increased to 600-650℃, and then a constant temperature heat treatment is carried out at 650-655℃ for 100-180min, and after it naturally drops to room temperature, the introduction of the mixed gas of Ar and C2H2 is finally stopped.

[0022] The advantage of adopting the present invention is that, through the CVD method, acetylene is decomposed at high temperature and uniformly deposited on the surface of nanoporous silicon to form a carbon layer. This uniform deposition characteristic helps to form a stable carbon coating structure, improves the conductivity of nanoporous silicon, and is beneficial to the transmission of electrons in the material, thereby improving the electrochemical performance of the negative electrode material. The CVD method has the advantages of simple process flow and easy operation, which helps to reduce production costs and improve production efficiency.

[0023] The third technical objective of the present invention is achieved through the following technical solutions: Preferably, step (6) the controllable preparation of the gas phase silicon-carbon negative electrode material of the porous carbon substrate The silicon / porous carbon composite material prepared in step (2) and the porous silicon acetylene carbon-coated by CVD method in step (5) are added as precursors. The precursors are placed in a tube furnace and heated to 500-700° C. for 1-5 hours in a CO2 atmosphere. After the reaction, the magnesium oxide in the intermediate product is removed by hydrochloric acid solution. The porous carbon-based gas-phase silicon-carbon negative electrode material is obtained by washing, filtering and vacuum drying.

[0024] The advantages of adopting the present invention are that by heating in a CO2 atmosphere, the generation of harmful gases can be avoided, and it is a green synthesis method; the porosity of silicon in the composite material and the content and thickness of the carbon coating layer can be regulated by changing the reaction temperature, and the continuous porous structure can reduce the volume effect, promote the diffusion of the electrolyte and accelerate the transmission of lithium ions; the uniform carbon coating layer can improve the electronic conductivity to promote the rapid transmission of ions, and can also serve as a protective layer to buffer the volume change of silicon during the cycle and inhibit the continuous growth of the solid electrolyte membrane.

[0025] It further consolidates the bond between silicon and porous carbon, enhances the overall structural stability of the material, has good resistance to volume changes of the negative electrode material during charging and discharging, and helps to improve the cycle life of the battery. During the heat treatment process, the pore structure of the porous carbon will be further optimized to form a channel that is more conducive to lithium ion transmission.

[0026] In summary, the present invention has the following beneficial effects: 1. The present invention has the advantage that, through the synergistic action of α-amylase and glucoamylase, raw starch is hydrolyzed from the outside to the inside, generating a large number of micropores, and forming porous starch with a high specific surface area; this porous structure not only increases the specific surface area of ​​the material, but also provides more attachment points and reaction space for subsequent vapor phase silicon deposition; 2. The present invention has the advantage that the high specific surface area and good adsorption performance of the porous starch are helpful for better adsorption and fixation of silicon nanoparticles in the subsequent steps, and are helpful for uniform distribution and firm attachment of silicon nanoparticles on the carbon substrate; 3. The present invention has the advantage that silicon nanoparticles can be uniformly and stably embedded in the porous structure through porous starch to form a silicon / porous carbon composite material, thereby improving the dispersibility of silicon nanoparticles and effectively alleviating the volume expansion problem of silicon during the charge and discharge process, thereby improving the cycle stability of the material; 4. The advantages of the present invention are that the addition of sucrose solution further enhances the bonding force between silicon nanoparticles and the porous carbon substrate, and the carbon layer can also provide additional conductivity and structural stability, which helps to maintain the integrity of the material and the consistency of performance during the charge and discharge process; 5. The present invention has the advantages that the micron porous Mg2Si structure is conducive to the insertion and extraction of lithium ions, and improves the electrochemical performance of the negative electrode material. By adjusting the concentration of the sodium hydroxide solution and the corrosion time, the pore structure of the Mg2Si negative electrode can be finely controlled, including the pore size, distribution and connectivity, and the performance of the negative electrode material can be further optimized. The micron porous Mg2Si negative electrode can provide more lithium storage sites due to its porous structure and high specific surface area; 6. The present invention has the advantage that the chemical reagents used in the whole preparation process, such as hydrochloric acid, Tris buffer, etc., are used in moderate amounts, are easy to handle, and meet environmental protection requirements; 7. The present invention has the advantage that a uniform carbon coating is formed on the surface of nanoporous silicon through polymerization of dopamine and subsequent carbonization treatment. This carbon coating can not only improve the conductivity of the material, but also effectively alleviate the volume expansion of silicon during the charge and discharge process, thereby improving the cycle stability and structural integrity of the material. 8. The present invention has the advantage that, through the CVD method, acetylene is decomposed at high temperature and uniformly deposited on the surface of nanoporous silicon to form a carbon layer. This uniform deposition property helps to form a stable carbon coating structure, improves the conductivity of nanoporous silicon, and is conducive to the transmission of electrons in the material, thereby improving the electrochemical performance of the negative electrode material. The CVD method has the advantages of simple process flow and convenient operation, which helps to reduce production costs and improve production efficiency. 9. The advantages of the present invention are that the generation of harmful gases can be avoided by heating in a CO2 atmosphere, and it is a green synthesis method; the porosity of silicon in the composite material and the content and thickness of the carbon coating layer can be regulated by changing the reaction temperature, and the continuous porous structure can reduce the volume effect, promote the diffusion of the electrolyte and accelerate the transmission of lithium ions; the uniform carbon coating layer can improve the electronic conductivity to promote the rapid transmission of ions, and can also serve as a protective layer to buffer the volume change of silicon during the cycle and inhibit the continuous growth of the solid electrolyte membrane; 10. The advantages of adopting the present invention are that the bonding between silicon and porous carbon is further stabilized, the overall structural stability of the material is enhanced, and the negative electrode material has good resistance to volume changes during charging and discharging, which helps to improve the cycle life of the battery. During the heat treatment process, the pore structure of the porous carbon will be further optimized to form a channel that is more conducive to lithium ion transmission. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a flow chart for preparing a gas phase silicon-carbon negative electrode material based on a porous carbon substrate of the present invention. DETAILED DESCRIPTION

[0028] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Without departing from the spirit and substance of the present invention, modifications or substitutions made to the methods, steps or conditions of the present invention are within the scope of the present invention.

[0029] If not specifically stated, the technical means used in the examples are conventional means known to those skilled in the art. In addition, all the raw materials used in the examples are known commercial products. Example 1

[0030] Step (1) Preparation of porous starch The corn starch is added to a sodium hydrogen phosphate-citric acid buffer solution with a pH value of 5.2, stirred and mixed, and pretreated at 55° C. for 30 minutes to obtain corn starch, α-amylase and glucoamylase are added to the pretreated starch suspension at a ratio of 1:3.5, and hydrolyzed on a magnetic stirrer at 45° C. and 180 r / min for 12 hours, after the enzymatic hydrolysis, a large number of micropores are generated in the raw starch from the outside to the inside, forming porous starch and starch slurry with high specific surface area and good adsorption performance, which are filtered and separated to obtain porous starch; Step (2) Preparation of silicon / porous carbon composite material The porous starch prepared in step (1) and deionized water (volume ratio of 1.5:100) are added to a magnetic stirrer at a constant temperature of 45°C, and a starch suspension is obtained at a stirring speed of 300 r / min. The silicon solution is then dispersed uniformly by ultrasonic treatment in advance to obtain a silicon-intercalated starch mixture. After 3 hours, a sucrose solution is added and dried in an oven at 40°C to obtain a sucrose-coated composite material. Finally, the porous starch / silicon / sucrose precursor is placed in an inert atmosphere of argon or nitrogen and carbonized at a high temperature. The starch reacts during the vacuum carbonization process, thereby obtaining a high-capacity silicon / porous carbon composite material with good cycle performance. Step (3) Preparation of microporous Mg2Si negative electrode The Mg-55Si thin slice was polished with sandpaper from coarse to fine, and then ultrasonically cleaned with deionized water and ethanol to remove the oxide layer and attached impurities generated on the surface of the sample during wire cutting to avoid affecting the subsequent dealloying treatment; the polished and cleaned sample was placed in a beaker containing 5wt.% sodium hydroxide solution, and the beaker was placed in a 70°C water bath for corrosion for 5 hours and then taken out, the sodium hydroxide solution attached to the surface of the sample was washed off, and the sample was placed in a vacuum drying oven and dried at 70°C for 12 hours to obtain a micron porous Mg2Si negative electrode; Step (4) Preparation of nanoporous silicon / carbon composite negative electrode The microporous Mg2Si negative electrode prepared in step (3) was placed in a muffle furnace at 550°C, and heat treated for 20 hours in an air atmosphere, and then the sample was taken out; the heat-treated sample was placed in a beaker containing a 5wt.% hydrochloric acid solution, and after corrosion at room temperature for 24 hours, the sample was taken out, the hydrochloric acid solution attached to the surface was washed off, and the sample was dried in a vacuum drying oven to obtain a nanoporous silicon sample; a Tris buffer solution with a concentration of 0.1M (pH=8.5) was prepared; 1.0g of the nanoporous silicon sample was weighed on a balance and placed in 100ml of the buffer solution, and magnetically stirred for 30 minutes to evenly disperse the sample in the solution to form a suspension; 1.0g of dopamine hydrochloride was added to the suspension, and magnetically stirred for 24 hours, and the sample was washed with deionized water, filtered, and vacuum dried for 12 hours; the vacuum-dried sample was placed in a tubular furnace, argon was introduced to expel the air, and then the temperature was increased for carbonization. The carbonization process was carried out in an argon protective atmosphere at a rate of 5°C min -1 The temperature was raised to 800°C at a rate of 1.5°C and kept at this temperature for 3 hours to obtain a nanoporous silicon / carbon composite negative electrode; Step (5) Carbon coating of porous silicon by acetylene CVD method A layer of the nanoporous silicon / carbon composite negative electrode prepared in step (4) is laid on the bottom of the quartz boat, and the quartz boat is placed in the middle position of the quartz tube of the tube furnace, and then the pipeline of the reaction system is connected; a mixed gas of Ar and C2H2 is introduced into the tube furnace at a gas flow rate of 300 ml / min, and the gas is heated at the same time, and the heating rate is set to 5°C / min, and the temperature is gradually increased to 650°C, and then a constant temperature heat treatment is performed at 650°C for 180 minutes, and after it naturally drops to room temperature, the introduction of the mixed gas of Ar and C2H2 is finally stopped; Step (6) Controllable preparation of gas phase silicon-carbon negative electrode material on porous carbon substrate The silicon / porous carbon composite material prepared in step (2) and the porous silicon acetylene carbon-coated by CVD method in step (5) are added as precursors. The precursors are placed in a tube furnace and heated to 550° C. for 2 hours in a CO2 atmosphere. After the reaction, the magnesium oxide in the intermediate product is removed by hydrochloric acid solution. The porous carbon-based gas-phase silicon-carbon negative electrode material is obtained by washing, filtering and vacuum drying. Example 2

[0031] Step (1) Preparation of porous starch The corn starch is added to a sodium hydrogen phosphate-citric acid buffer solution with a pH value of 3, stirred and mixed, and pretreated at 45° C. for 25 minutes to obtain corn starch, α-amylase and glucoamylase are added to the pretreated starch suspension at a ratio of 1:2, and hydrolyzed on a magnetic stirrer at 40° C. and 150 r / min for 9 hours, after the enzymatic hydrolysis, a large number of micropores are generated in the raw starch from the outside to the inside, forming porous starch and starch slurry with high specific surface area and good adsorption performance, which are filtered and separated to obtain porous starch; Step (2) Preparation of silicon / porous carbon composite material The porous starch prepared in step (1) and deionized water (volume ratio of 1:95) are added to a magnetic stirrer at a constant temperature of 40°C, and a starch suspension is obtained at a stirring speed of 250 r / min. The silicon solution is then dispersed uniformly by ultrasonic treatment in advance to obtain a silicon-intercalated starch mixture. After 1 hour, a sucrose solution is added and dried in an oven at 40°C to obtain a sucrose-coated composite material. Finally, the porous starch / silicon / sucrose precursor is placed in an inert atmosphere of argon or nitrogen and carbonized at a high temperature. The starch reacts during the vacuum carbonization process, thereby obtaining a high-capacity silicon / porous carbon composite material with good cycle performance. Step (3) Preparation of microporous Mg2Si negative electrode The Mg-55Si thin slice was polished with sandpaper from coarse to fine, and then ultrasonically cleaned with deionized water and ethanol to remove the oxide layer and attached impurities generated on the surface of the sample during wire cutting to avoid affecting the subsequent dealloying treatment; the polished and cleaned sample was placed in a beaker containing 1wt.% sodium hydroxide solution, and the beaker was placed in a 65°C water bath for corrosion for 1h and then taken out, the sodium hydroxide solution attached to the surface of the sample was washed off, and the sample was placed in a vacuum drying oven and dried at 65°C for 8h to obtain a micron porous Mg2Si negative electrode; Step (4) Preparation of nanoporous silicon / carbon composite negative electrode The microporous Mg2Si negative electrode prepared in step (3) was placed in a muffle furnace at 400°C, and heat treated for 15 hours in an air atmosphere, and then the sample was taken out; the heat-treated sample was placed in a beaker containing a 1wt.% hydrochloric acid solution, and after corrosion at room temperature for 12 hours, the sample was taken out, the hydrochloric acid solution attached to the surface was washed off, and the sample was dried in a vacuum drying oven to obtain a nanoporous silicon sample; a Tris buffer solution with a concentration of 0.1M (pH=6) was prepared; 1.0g of the nanoporous silicon sample was weighed on a balance and placed in 95ml of the buffer solution, and magnetically stirred for 25 minutes to evenly disperse the sample in the solution to form a suspension; 1.0g of dopamine hydrochloride was added to the suspension, and magnetically stirred for 12 hours, and the sample was washed with deionized water, filtered, and vacuum dried for 6 hours; the vacuum-dried sample was placed in a tubular furnace, argon was introduced to expel the air, and then the temperature was increased for carbonization. The carbonization process was carried out in an argon protective atmosphere at a rate of 1°C min -1 The temperature was raised to 750°C at a rate of 1.5°C and kept at this temperature for 1 hour to obtain a nanoporous silicon / carbon composite negative electrode; Step (5) Carbon coating of porous silicon by acetylene CVD method A layer of the nanoporous silicon / carbon composite negative electrode prepared in step (4) is laid on the bottom of the quartz boat, and the quartz boat is placed in the middle position of the quartz tube of the tube furnace, and then the pipeline of the reaction system is connected; a mixed gas of Ar and C2H2 is introduced into the tube furnace at a gas flow rate of 300 ml / min, and the gas is heated at the same time, and the heating rate is set to 6°C / min, and the temperature is gradually increased to 600°C, and then a constant temperature heat treatment is performed at 650°C for 180 minutes, and after it naturally drops to room temperature, the introduction of the mixed gas of Ar and C2H2 is finally stopped; Step (6) Controllable preparation of gas phase silicon-carbon negative electrode material on porous carbon substrate The silicon / porous carbon composite material prepared in step (2) and the porous silicon acetylene carbon-coated by CVD method in step (5) are added as precursors. The precursors are placed in a tube furnace and heated to 500° C. for 1 hour in a CO2 atmosphere. After the reaction, the magnesium oxide in the intermediate product is removed by hydrochloric acid solution. The porous carbon-based gas-phase silicon-carbon negative electrode material is obtained by washing, filtering and vacuum drying. Example 3

[0032] Step (1) Preparation of porous starch The corn starch is added to a sodium hydrogen phosphate-citric acid buffer solution with a pH value of 5, stirred and mixed, and pretreated at 46° C. for 26 minutes to obtain corn starch, α-amylase and glucoamylase are added to the pretreated starch suspension at a ratio of 2:2, and hydrolyzed on a magnetic stirrer at 42° C. and 160 r / min for 10 hours, after the enzymatic hydrolysis, a large number of micropores are generated in the raw starch from the outside to the inside, forming porous starch and starch slurry with high specific surface area and good adsorption performance, which are filtered and separated to obtain porous starch; Step (2) Preparation of silicon / porous carbon composite material The porous starch prepared in step (1) and deionized water (volume ratio of 3:100) are added to a magnetic stirrer at a constant temperature of 42°C, and a starch suspension is obtained at a stirring speed of 260 r / min. The silicon solution is then dispersed uniformly by ultrasonic treatment in advance to obtain a silicon-intercalated starch mixture. After 2 hours, a sucrose solution is added and dried in an oven at 43°C to obtain a sucrose-coated composite material. Finally, the porous starch / silicon / sucrose precursor is placed in an inert atmosphere of argon or nitrogen and carbonized at a high temperature. The starch reacts during the vacuum carbonization process, thereby obtaining a high-capacity silicon / porous carbon composite material with good cycle performance. Step (3) Preparation of microporous Mg2Si negative electrode The Mg-55Si thin slice was polished with sandpaper from coarse to fine, and then ultrasonically cleaned with deionized water and ethanol to remove the oxide layer and attached impurities generated on the surface of the sample during wire cutting to avoid affecting the subsequent dealloying treatment; the polished and cleaned sample was placed in a beaker containing 3wt.% sodium hydroxide solution, and the beaker was placed in a 66°C water bath for corrosion for 3h and then taken out, the sodium hydroxide solution attached to the surface of the sample was washed off, and the sample was placed in a vacuum drying oven and dried at 66°C for 10h to obtain a micron porous Mg2Si negative electrode; Step (4) Preparation of nanoporous silicon / carbon composite negative electrode The microporous Mg2Si negative electrode prepared in step (3) was placed in a muffle furnace at 410°C, and heat treated for 16 hours in an air atmosphere, and then the sample was taken out; the heat-treated sample was placed in a beaker containing a 3wt.% hydrochloric acid solution, and after corrosion at room temperature for 14 hours, the sample was taken out, the hydrochloric acid solution attached to the surface was washed off, and the sample was dried in a vacuum drying oven to obtain a nanoporous silicon sample; a Tris buffer solution with a concentration of 0.3M (pH=7) was prepared; 3.0g of the nanoporous silicon sample was weighed on a balance and placed in 96ml of the buffer solution, and magnetically stirred for 26 minutes to evenly disperse the sample in the solution to form a suspension; 2.0g of dopamine hydrochloride was added to the suspension, and magnetically stirred for 14 hours, and the sample was washed with deionized water, filtered, and vacuum dried for 10 hours; the vacuum-dried sample was placed in a tubular furnace, argon was introduced to expel the air, and then the temperature was increased for carbonization. The carbonization process was carried out in an argon protective atmosphere at a rate of 2°C min -1 The temperature was raised to 760°C at a rate of 1.50°C and kept at this temperature for 2 hours to obtain a nanoporous silicon / carbon composite negative electrode; Step (5) Carbon coating of porous silicon by acetylene CVD method A layer of the nanoporous silicon / carbon composite negative electrode prepared in step (4) is laid on the bottom of the quartz boat, and the quartz boat is placed in the middle position of the quartz tube of the tube furnace, and then the pipeline of the reaction system is connected; a mixed gas of Ar and C2H2 is introduced into the tube furnace, and the gas flow rate is 315 ml / min. At the same time, the gas is heated, and the heating rate is set to 6°C / min. The temperature is gradually increased to 650°C, and then a constant temperature heat treatment is performed at 650°C for 180 minutes. After the mixture is naturally cooled to room temperature, the introduction of the mixed gas of Ar and C2H2 is finally stopped; Step (6) Controllable preparation of gas phase silicon-carbon negative electrode material on porous carbon substrate The silicon / porous carbon composite material prepared in step (2) and the porous silicon acetylene carbon-coated by CVD method in step (5) are added as precursors. The precursors are placed in a tube furnace and heated to 550° C. for 3 hours in a CO2 atmosphere. After the reaction, the magnesium oxide in the intermediate product is removed by hydrochloric acid solution. The porous carbon-based gas-phase silicon-carbon negative electrode material is obtained by washing, filtering and vacuum drying. Example 4

[0033] Step (1) Preparation of porous starch The corn starch is added to a sodium hydrogen phosphate-citric acid buffer solution with a pH value of 6, stirred and mixed, and pretreated at 55° C. for 30 minutes to obtain corn starch, α-amylase and glucoamylase are added to the pretreated starch suspension at a ratio of 2:4, and hydrolyzed on a magnetic stirrer at 45° C. and 180 r / min for 15 hours, after the enzymatic hydrolysis, a large number of micropores are generated in the raw starch from the outside to the inside, forming porous starch and starch slurry with high specific surface area and good adsorption performance, which are filtered and separated to obtain porous starch; Step (2) Preparation of silicon / porous carbon composite material The porous starch prepared in step (1) and deionized water (volume ratio of 3:100) are added to a magnetic stirrer at a constant temperature of 43°C, and a starch suspension is obtained at a stirring speed of 260 r / min. The silicon solution is then dispersed uniformly by ultrasonic treatment in advance to obtain a silicon-intercalated starch mixture. After 4 hours, a sucrose solution is added and dried in an oven at 44°C to obtain a sucrose-coated composite material. Finally, the porous starch / silicon / sucrose precursor is placed in an inert atmosphere of argon or nitrogen and carbonized at a high temperature. The starch reacts during the vacuum carbonization process, thereby obtaining a high-capacity silicon / porous carbon composite material with good cycle performance. Step (3) Preparation of microporous Mg2Si negative electrode The Mg-55Si thin slice was polished with sandpaper from coarse to fine, and then ultrasonically cleaned with deionized water and ethanol to remove the oxide layer and attached impurities generated on the surface of the sample during wire cutting to avoid affecting the subsequent dealloying treatment; the polished and cleaned sample was placed in a beaker containing 3wt.% sodium hydroxide solution, and the beaker was placed in a 66°C water bath for corrosion for 5 hours and then taken out, the sodium hydroxide solution attached to the surface of the sample was washed off, and the sample was placed in a vacuum drying oven and dried at 68°C for 10 hours to obtain a micron porous Mg2Si negative electrode; Step (4) Preparation of nanoporous silicon / carbon composite negative electrode The microporous Mg2Si negative electrode prepared in step (3) was placed in a muffle furnace at 350°C, and heat treated for 16 hours in an air atmosphere, and then the sample was taken out; the heat-treated sample was placed in a beaker containing a 3wt.% hydrochloric acid solution, and after corrosion at room temperature for 15 hours, the sample was taken out, the hydrochloric acid solution attached to the surface was washed off, and the sample was dried in a vacuum drying oven to obtain a nanoporous silicon sample; a Tris buffer solution with a concentration of 0.2M (pH=7) was prepared; 2.0g of the nanoporous silicon sample was weighed on a balance and placed in 96ml of the buffer solution, and magnetically stirred for 26 minutes to evenly disperse the sample in the solution to form a suspension; 2.0g of dopamine hydrochloride was added to the suspension, and magnetically stirred for 14 hours, and the sample was washed with deionized water, filtered, and vacuum dried for 10 hours; the vacuum-dried sample was placed in a tubular furnace, argon was introduced to expel the air, and then the temperature was increased for carbonization. The carbonization process was carried out in an argon protective atmosphere at a rate of 2°C min -1 The temperature was raised to 760°C at a rate of 1.50°C and kept at this temperature for 2 hours to obtain a nanoporous silicon / carbon composite negative electrode; Step (5) Carbon coating of porous silicon by acetylene CVD method A layer of nanoporous silicon / carbon composite negative electrode prepared in step (4) is laid on the bottom of the quartz boat, and the quartz boat is placed in the middle position of the quartz tube of the tube furnace, and then the pipeline of the reaction system is connected; a mixed gas of Ar and C2H2 is introduced into the tube furnace, and the gas flow rate is 320 ml / min. At the same time, the gas is heated, and the heating rate is set to 6°C / min. The temperature is gradually increased to 650°C, and then a constant temperature heat treatment is performed at 650°C for 110 minutes. After the mixture is naturally cooled to room temperature, the introduction of the mixed gas of Ar and C2H2 is finally stopped; Step (6) Controllable preparation of gas phase silicon-carbon negative electrode material on porous carbon substrate The silicon / porous carbon composite material prepared in step (2) and the porous silicon acetylene carbon-coated by CVD method in step (5) are added as precursors. The precursors are placed in a tube furnace and heated to 550° C. for 2 hours in a CO2 atmosphere. After the reaction, the magnesium oxide in the intermediate product is removed by hydrochloric acid solution. The porous carbon-based gas-phase silicon-carbon negative electrode material is obtained by washing, filtering and vacuum drying. Comparative Example 1

[0034] Step (1) Preparation of porous starch The corn starch is added to a sodium hydrogen phosphate-citric acid buffer solution with a pH value of 10, stirred and mixed, and pretreated at 60° C. for 60 minutes to obtain corn starch, α-amylase and glucoamylase are added to the pretreated starch suspension at a ratio of 3:5, and hydrolyzed on a magnetic stirrer at 50° C. and 200 r / min for 24 hours, after the enzymatic hydrolysis, a large number of micropores are generated in the raw starch from the outside to the inside, forming porous starch and starch slurry with high specific surface area and good adsorption performance, which are filtered and separated to obtain porous starch; Step (2) Preparation of silicon / porous carbon composite material The porous starch prepared in step (1) and deionized water (volume ratio of 4:100) are added to a magnetic stirrer at a constant temperature of 50°C, and a starch suspension is obtained at a stirring speed of 350 r / min. The silicon solution is then dispersed uniformly by ultrasonic treatment in advance to obtain a silicon-intercalated starch mixture. After 3 hours, a sucrose solution is added and dried in an oven at 50°C to obtain a sucrose-coated composite material. Finally, the porous starch / silicon / sucrose precursor is placed in an inert atmosphere of argon or nitrogen and carbonized at a high temperature. The starch reacts during the vacuum carbonization process, thereby obtaining a high-capacity silicon / porous carbon composite material with good cycle performance. Step (3) Preparation of nanoporous silicon / carbon composite negative electrode The silicon / porous carbon composite material prepared in step (2) was placed in a muffle furnace at 600°C, and heat treated for 24 hours in an air atmosphere, and then the sample was taken out; the heat-treated sample was placed in a beaker containing a 6wt.% hydrochloric acid solution, and after corrosion at room temperature for 24 hours, the sample was taken out, the hydrochloric acid solution attached to the surface was washed off, and the sample was dried in a vacuum drying oven to obtain a nanoporous silicon sample; a Tris buffer solution (pH=9) with a concentration of 0.3M was prepared; 6.0g of the nanoporous silicon sample was weighed on a balance and placed in 100ml of the buffer solution, and magnetically stirred for 35 minutes to evenly disperse the sample in the solution to form a suspension; 6.0g of dopamine hydrochloride was added to the suspension, and magnetically stirred for 24 hours, and the sample was washed with deionized water, filtered, and vacuum dried for 12 hours; the vacuum-dried sample was placed in a tubular furnace, argon was introduced to expel the air, and then the temperature was increased for carbonization. The carbonization process was carried out in an argon protective atmosphere at a rate of 5°C min -1 The temperature was raised to 800°C at a rate of 1.50°C and kept at this temperature for 5 hours to obtain a nanoporous silicon / carbon composite negative electrode; Step (4) Carbon coating of porous silicon by acetylene CVD method A layer of nanoporous silicon / carbon composite negative electrode prepared in step (3) is laid on the bottom of the quartz boat, and the quartz boat is placed in the middle position of the quartz tube of the tube furnace, and then the pipeline of the reaction system is connected; a mixed gas of Ar and C2H2 is introduced into the tube furnace, and the gas flow rate is 400ml / min. At the same time, the gas is heated, and the heating rate is set to 15℃ / min. The temperature is gradually increased to 700℃, and then a constant temperature heat treatment is performed at 655℃ for 180min. After the mixture is naturally cooled to room temperature, the introduction of the mixed gas of Ar and C2H2 is finally stopped; Step (5) Controllable preparation of gas phase silicon-carbon negative electrode material on porous carbon substrate The silicon / porous carbon composite material prepared in step (2) and the porous silicon acetylene carbon-coated by CVD method in step (4) are added as precursors. The precursors are placed in a tube furnace and heated to 700° C. for 6 hours in a CO2 atmosphere. After the reaction, the magnesium oxide in the intermediate product is removed by hydrochloric acid solution. The porous carbon-based gas-phase silicon-carbon negative electrode material is obtained by washing, filtering and vacuum drying. Comparative Example 2

[0035] Step (1) Preparation of porous starch The corn starch is added to a sodium hydrogen phosphate-citric acid buffer solution with a pH value of 12, stirred and mixed, and pretreated at 35° C. for 25 minutes to obtain corn starch, α-amylase and glucoamylase are added to the pretreated starch suspension at a ratio of 3:5, and hydrolyzed on a magnetic stirrer at 50° C. and 200 r / min for 20 hours, after the enzymatic hydrolysis, a large number of micropores are generated in the raw starch from the outside to the inside, forming porous starch and starch slurry with high specific surface area and good adsorption performance, which are filtered and separated to obtain porous starch; Step (2) Preparation of silicon / porous carbon composite material The porous starch prepared in step (1) and deionized water (volume ratio of 4:120) are added to a magnetic stirrer at a constant temperature of 50°C, and a starch suspension is obtained at a stirring speed of 320 r / min. The silicon solution is then dispersed uniformly by ultrasonic treatment in advance to obtain a silicon-intercalated starch mixture. After 4 hours, a sucrose solution is added and dried in an oven at 50°C to obtain a sucrose-coated composite material. Finally, the porous starch / silicon / sucrose precursor is placed in an inert atmosphere of argon or nitrogen and carbonized at a high temperature. The starch reacts during the vacuum carbonization process, thereby obtaining a high-capacity silicon / porous carbon composite material with good cycle performance. Step (3) Preparation of microporous Mg2Si negative electrode The Mg-55Si thin slice was polished with sandpaper from coarse to fine, and then ultrasonically cleaned with deionized water and ethanol to remove the oxide layer and attached impurities generated on the surface of the sample during wire cutting to avoid affecting the subsequent dealloying treatment; the polished and cleaned sample was placed in a beaker containing 6wt.% sodium hydroxide solution, and the beaker was placed in a 75°C water bath for corrosion for 3h and then taken out, the sodium hydroxide solution attached to the surface of the sample was washed off, and the sample was placed in a vacuum drying oven and dried at 75°C for 15h to obtain a micron porous Mg2Si negative electrode; Step (4) Preparation of nanoporous silicon / carbon composite negative electrode The microporous Mg2Si negative electrode prepared in step (3) is placed in a muffle furnace at 400-550°C, and heat treated for 15-20 hours in an air atmosphere, and then the sample is taken out; the heat-treated sample is placed in a beaker containing a 1-5wt.% hydrochloric acid solution, and after corrosion at room temperature for 12-24 hours, the sample is taken out, the hydrochloric acid solution attached to the surface is washed off, and the sample is dried in a vacuum drying oven to obtain a nanoporous silicon sample; a Tris buffer solution (pH= 0.1-0.5M) is prepared. 6-8.5); weigh 1.0-5.0g of nanoporous silicon sample with a balance and put it into 120ml buffer solution, stir magnetically for 35min, and evenly disperse the sample into the solution to form a suspension; add 6.0g of dopamine hydrochloride into the suspension, stir magnetically for 24h, wash with deionized water, filter, and vacuum dry for 15h; put the vacuum-dried sample into a tubular furnace, introduce argon gas to exhaust the air, and then heat and carbonize. The carbonization process is carried out in an argon protective atmosphere at 6℃min -1 The temperature was raised to 770°C at a rate of 100°C and kept at that temperature for 1-3 hours to obtain a nanoporous silicon / carbon composite negative electrode; Step (5) Controllable preparation of gas phase silicon-carbon negative electrode material on porous carbon substrate The silicon / porous carbon composite material prepared in step (2) and the nanoporous silicon / carbon composite negative electrode prepared in step (4) are added as precursors. The precursors are placed in a tube furnace and heated to 600° C. for 2 hours in a CO2 atmosphere. After the reaction, the magnesium oxide in the intermediate product is removed by a hydrochloric acid solution. The porous carbon-based gas-phase silicon-carbon negative electrode material is obtained by washing, filtering and vacuum drying.

[0036] Comparison of detection experiments: The porous carbon substrate gas phase silicon carbon negative electrode materials obtained in Examples 1 to 4 and the comparative examples 1 and 2 were tested. The specific testing method is as follows: Specific surface area test Nitrogen adsorption method (BET method): This is the most commonly used method for testing the specific surface area of ​​porous materials. By measuring the amount of nitrogen adsorbed by the sample at low temperature and using the BET (Brunauer-Emmett-Teller) equation to calculate the specific surface area, it may be more accurate and sensitive than the low-temperature nitrogen adsorption method for materials with smaller pore sizes.

[0037] Pore ​​size distribution test Nuclear magnetic resonance nanopore analysis (NMRC): This is an emerging testing technology that uses nuclear magnetic resonance technology to test the phase change process of liquid in pores and characterizes the pore size distribution of porous materials through the Gibbs-Thomson equation. This method has a wide detection range and can reflect more pore types (including open pores and closed pores).

[0038] Particle size testing A grading method that uses sieve holes to mechanically block powders. According to the particle size and distribution range of the tested sample, sieves with different sizes of sieve holes are stacked together for screening. The mass of the remaining samples on different sieves is weighed, and the particle size distribution of the sample with the sieve hole diameter as the boundary is calculated. The screening method is divided into dry screening (direct screening without the help of solvents) and wet screening (screening with solvents such as water and ethanol) according to different test conditions. The particle size measured by the screening method is the equivalent screening diameter, that is, the diameter of spherical particles of the same substance passing through the same sieve hole under the same screening conditions.

[0039] Table 1 Specific surface area test

[0040] As can be seen from Table 1, Example 1 is the best and the comparative example is worse. The specific surface area of ​​Example 1 is relatively large. The micron porous Mg2Si structure in the example is conducive to the embedding and extraction of lithium ions, further optimizing the performance of the negative electrode material. In addition, the micron porous Mg2Si negative electrode has a porous structure and a high specific surface area. The larger specific surface area has more active sites and can embed more lithium ions, thereby potentially increasing the lithium storage capacity of the material. The larger specific surface area in Comparative Example 1 may also cause the material to have more side reactions with the electrolyte during the charge and discharge process. When the pore structure in Comparative Example 2 is almost completely filled or destroyed, its specific surface area tends to the minimum value, which will seriously limit its lithium storage capacity and reaction rate.

[0041] Table 2 Pore size distribution test

[0042] As can be seen from Table 2, Example 1 is the best, while Comparative Example 2 is relatively poor. The nanopore size of the porous carbon substrate in Example 1 is relatively small, which is conducive to providing more active sites, increasing the contact area between the material and the electrolyte, and can effectively alleviate the huge volume expansion of silicon during the charge and discharge process. The nanopore size provides sufficient space for the volume change of silicon, reduces the breakage and pulverization of silicon particles, and thus improves the structural stability of the negative electrode material. This uniform dispersion reduces the agglomeration phenomenon between silicon particles and improves the utilization rate of silicon.

[0043] Table 3 Particle size test

[0044] As can be seen from Table 3, Example 1 is the best and Comparative Example 2 is relatively poor. The particle size in Example 1 is the smallest, and the smaller the particle size, the larger the specific surface area. In the embodiment, acetylene is decomposed at high temperature and uniformly deposited on the surface of nanoporous silicon to form a carbon layer by CVD method. This uniform deposition property helps to form a stable carbon coating structure. At the same time, the reduction of particle size helps to shorten the transmission path of lithium ions and other electrolyte ions in the material and improve the diffusion rate of ions.

[0045] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art can make non-creative modifications to the present embodiment as needed, but they are protected by patent law as long as they are within the scope of the claims of the present invention.

Claims

1. A porous carbon-based gas-phase silicon-carbon negative electrode material, characterized in that: include: Preparation of porous starch, preparation of silicon / porous carbon composite materials, preparation of micron porous Mg2Si negative electrode, preparation of nanoporous silicon / carbon composite negative electrode, carbon coating of porous silicon by acetylene CVD method, and controllable preparation of gas phase silicon-carbon negative electrode materials on porous carbon substrate.

2. The porous carbon-based gas-phase silicon-carbon negative electrode material according to claim 1, characterized in that: Step (1) Preparation of porous starch The corn starch is added into a sodium hydrogen phosphate-citric acid buffer solution, stirred and mixed, and pretreated to obtain corn starch, α-amylase and glucoamylase are added into the pretreated starch suspension, and hydrolyzed on a magnetic stirrer, after the enzymatic hydrolysis, a large number of micropores are generated from the outside to the inside of the raw starch, forming porous starch and starch slurry with high specific surface area and good adsorption performance, and the porous starch is separated by filtering; Step (2) Preparation of silicon / porous carbon composite material The porous starch prepared in step (1) and deionized water are added to a magnetic stirrer to obtain a starch suspension, and then the silicon solution is dispersed uniformly by ultrasonic treatment in advance to obtain a starch mixture in which silicon is inserted, and then a sucrose solution is added, and the mixture is dried in an oven to obtain a sucrose-coated composite material, and finally the porous starch / silicon / sucrose precursor is placed in an inert atmosphere of argon or nitrogen and carbonized at a high temperature, and the starch reacts during the vacuum carbonization process, thereby obtaining a high-capacity silicon / porous carbon composite material with good cycle performance; Step (3) Preparation of microporous Mg2Si negative electrode The Mg-55Si thin slice is polished by sandpaper from coarse to fine, and then ultrasonically cleaned with deionized water and ethanol to remove the oxide layer and attached impurities generated on the surface of the sample during wire cutting to avoid affecting the subsequent dealloying treatment; the polished and cleaned sample is then placed in a beaker containing sodium hydroxide solution, and the beaker is placed in a water bath for corrosion and then taken out, the sodium hydroxide solution attached to the surface of the sample is washed off, and the sample is placed in a vacuum drying oven for drying to obtain a micron porous Mg2Si negative electrode; Step (4) Preparation of nanoporous silicon / carbon composite negative electrode The microporous Mg2Si negative electrode prepared in step (3) is placed in a muffle furnace, and after heat treatment in an air atmosphere, a sample is taken out; the heat-treated sample is placed in a beaker containing a hydrochloric acid solution, and after corrosion at room temperature, the sample is taken out and the hydrochloric acid solution attached to the surface is washed off, and then dried in a vacuum drying oven to obtain a nanoporous silicon sample; a Tris buffer is prepared; the nanoporous silicon sample is weighed and placed in the buffer, and magnetically stirred to uniformly disperse the sample in the solution to form a suspension; dopamine hydrochloride is added to the suspension and magnetically stirred, and after washing and filtering with deionized water, the vacuum-dried sample is placed in a tubular furnace, and after passing argon gas to expel the air, the temperature is increased for carbonization, and the carbonization process is carried out in an argon protective atmosphere to obtain a nanoporous silicon / carbon composite negative electrode; Step (5) Carbon coating of porous silicon by acetylene CVD method A layer of the nanoporous silicon / carbon composite negative electrode prepared in step (4) is laid on the bottom of the quartz boat, and the quartz boat is placed in the middle position of the quartz tube of the tube furnace, and then the pipeline of the reaction system is connected; a mixed gas of Ar and C2H2 (acetylene) is introduced into the tube furnace, and the gas is heated at the same time, and then a constant temperature heat treatment is performed, and after the gas is naturally cooled to room temperature, the introduction of the mixed gas of Ar and C2H2 is finally stopped; Step (6) Controllable preparation of gas phase silicon-carbon negative electrode material on porous carbon substrate The silicon / porous carbon composite material prepared in step (2) and the porous silicon acetylene carbon-coated by CVD method in step (5) are added as precursors, and the precursors are placed in a tube furnace and heated in a CO2 atmosphere. After the reaction, the magnesium oxide in the intermediate product is removed by hydrochloric acid solution, and the gas phase silicon-carbon negative electrode material of the porous carbon substrate is obtained by washing, filtering and vacuum drying.

3. The porous carbon-based gas-phase silicon-carbon negative electrode material according to claim 2, characterized in that: Step (1) Preparation of porous starch Corn starch is added to a sodium hydrogen phosphate-citric acid buffer solution with a pH value of 3-6, stirred and mixed, and pretreated at 45-55° C. for 25-30 minutes to obtain corn starch, α-amylase and glucoamylase are added to the pretreated starch suspension at a ratio of 1-2:2-4, and hydrolyzed on a magnetic stirrer at 40-45° C. and 150-180 r / min for 9-15 hours. After enzymatic hydrolysis, a large number of micropores are generated in the raw starch from the outside to the inside, forming porous starch and starch slurry with high specific surface area and good adsorption performance, which are filtered and separated to obtain porous starch.

4. The porous carbon-based gas-phase silicon-carbon negative electrode material according to claim 3, characterized in that: Step (2) Preparation of silicon / porous carbon composite material The porous starch prepared in step (1) and deionized water (volume ratio of 1-3:95-100) are added to a magnetic stirrer at a constant temperature of 40-45°C, and a starch suspension is obtained at a stirring speed of 250-300 r / min. The silicon solution is then dispersed uniformly by ultrasonic treatment to obtain a silicon-intercalated starch mixture. After 1-3 hours, a sucrose solution is added and dried in an oven at 40-45°C to obtain a sucrose-coated composite material. Finally, the porous starch / silicon / sucrose precursor is placed in an inert atmosphere of argon or nitrogen and carbonized at high temperature. The starch reacts during the vacuum carbonization process to obtain a high-capacity silicon / porous carbon composite material with good cycle performance.

5. The porous carbon-based gas-phase silicon-carbon negative electrode material according to claim 2, characterized in that: Step (3) Preparation of microporous Mg2Si negative electrode The Mg-55Si thin slice was grinded and polished with sandpaper from coarse to fine, and then ultrasonically cleaned with deionized water and ethanol to remove the oxide layer and attached impurities generated on the surface of the sample during wire cutting to avoid affecting the subsequent dealloying treatment; the grinded, polished and cleaned sample was placed in a beaker containing 1-5wt.% sodium hydroxide solution, and the beaker was placed in a 65-70℃ water bath for corrosion for 1-5h and then taken out, the sodium hydroxide solution attached to the surface of the sample was washed off, and the sample was placed in a vacuum drying oven and dried at 65-70℃ for 8-12h to obtain a micron porous Mg2Si negative electrode.

6. The porous carbon-based gas-phase silicon-carbon negative electrode material according to claim 5, characterized in that: Step (4) Preparation of nanoporous silicon / carbon composite negative electrode The micron porous Mg2Si negative electrode prepared in step (3) is placed in a muffle furnace at 400-550°C, and heat treated for 15-20 hours in an air atmosphere, and then the sample is taken out; the heat-treated sample is placed in a beaker containing 1-5wt.% hydrochloric acid solution, and corroded at room temperature for 12-24 hours, and then the sample is taken out, and the hydrochloric acid solution attached to the surface is washed off, and then dried in a vacuum drying oven to obtain a nanoporous silicon sample; a Tris buffer solution (pH=6-8.5) with a concentration of 0.1-0.5M is prepared; and a 100% MgCl2O3 solution is added to the sample. Weigh 1.0-5.0g of nanoporous silicon sample and put it into 95-100ml buffer solution, stir magnetically for 25-30min, and evenly disperse the sample into the solution to form a suspension; add 1.0-5.0g of dopamine hydrochloride into the suspension, stir magnetically for 12-24h, wash with deionized water, filter, and vacuum dry for 6-12h; put the vacuum-dried sample into a tubular furnace, introduce argon gas to exhaust the air, and then heat and carbonize. The carbonization process is carried out in an argon protective atmosphere at a rate of 1-5℃min -1 The temperature is raised to 750-800°C at a rate of 100°C and kept at this temperature for 1-3 hours to obtain a nanoporous silicon / carbon composite negative electrode.

7. The porous carbon-based gas-phase silicon-carbon negative electrode material according to claim 6, characterized in that: Step (5) Carbon coating of porous silicon by acetylene CVD method A layer of nanoporous silicon / carbon composite negative electrode prepared in step (4) is laid on the bottom of the quartz boat, and the quartz boat is placed in the middle position of the quartz tube of the tube furnace, and then the pipeline of the reaction system is connected; a mixed gas of Ar and C2H2 is introduced into the tube furnace, and the gas flow rate is 300-350ml / min. At the same time, the gas is heated, and the heating rate is set to 5-10℃ / min, and the temperature is gradually increased to 600-650℃, and then a constant temperature heat treatment is carried out at 650-655℃ for 100-180min, and after it naturally drops to room temperature, the introduction of the mixed gas of Ar and C2H2 is finally stopped.

8. The porous carbon-based gas-phase silicon-carbon negative electrode material according to claim 7, characterized in that: Step (6) Controllable preparation of gas phase silicon-carbon negative electrode material on porous carbon substrate The silicon / porous carbon composite material prepared in step (2) and the porous silicon acetylene carbon-coated by CVD method in step (5) are added as precursors. In a CO2 atmosphere, the precursors are placed in a tube furnace and heated to 500-700°C for 1-5 hours. After the reaction, the magnesium oxide in the intermediate product is removed by hydrochloric acid solution. The porous carbon substrate gas phase silicon carbon negative electrode material is obtained by washing, filtering and vacuum drying.

Citation Information

Cited By

  • Negative electrode material, negative electrode sheet, and secondary battery

    WO2026148922A1